An introduction to early Irish literature - Ní Bhrolcháin, Muireann (Dublin ; Portland, OR : Four Courts Press, 2009)
A discussion of the rich written heritage of the Old and Middle Irish period, 600-1200. Chapters deal with such topics as druids, monks, poets, the beginnings of writing manuscripts, saga cycles, and stories about kings, kingship and sovereignty goddesses.
The background -- Stories and storytelling -- Druids, poets, and bards -- The arrival of Christianity -- Branches of literature -- Oral tradition and written literature -- Ogam, writing, and manuscripts -- An example of the language about 1000 -- The mythological cycle -- Addendum : theory -- The heroic cycle -- Discussion of the Táin -- The Fenian cycle -- The cycles of the kings -- The otherworld -- The location and nature of the otherworld -- Otherworld visits and the heroic biography -- The voyages and Brendan voyage -- The vision tales -- Kings, goddesses, and sovereignty -- Goddesses of sovereignty -- The manifestations of the sovereignty goddess -- Madness in early Irish literature -- The hero and heroic biography -- Conception and birth -- Account of youth and upbringing -- Invulnerability -- A fight with a dragon or a monster -- The hero acquires a wife -- The hero visits the otherworld -- Exile and return -- Death of the hero -- Poets and poetry -- The status of the poet -- Prosimetrum -- Poets and poetry -- Early Irish lyrics.
Includes bibliographical references (p. 171-190) and index.
Keywords: 600-1200; Irish literature -- To 1100 -- History and criticism; kirjallisuudenhistoria; Irlanti